OPTIMALISASI PENGELOLAAN, PEMANFAATAN DAN PENGAWASAN DANA DESA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA DI PROVINSI SUMATERA UTARA - Anton Parlindungan Sinaga (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2022)
This study aims to determine the management, utilization, and supervision of village funds to improve the economy of rural communities in North Sumatra Province. The locations determined are Deli Serdang Regency, Langkat Regency, Karo Regency and Batubara Regency. The method used is descriptive qualitative with data collection techniques in the form of observation, conducting in-depth interviews, distributing questionnaires and reviewing documentation. The data analysis technique used is the interactive model of Miles, Huberman and Saldana covering the stages of data collection, data condensation, data presentation and concluding. The results of the study found that 1) Overall the village fund management process in North Sumatra Province had been carried out following the procedures and laws and regulations which included the stages of planning, implementation, administration, accountability and reporting. 2) Utilization of village funds is used for village development through the development of village potential as an effort to increase PAD and the community's economy, namely through the establishment of BUMDes, but there are still limited human resources in managing it. 3) Supervision of village funds has been carried out following the standards and procedures regulated in Permendagri no. 73 of 2020 to optimize the supervision of village funds and minimize deviations and conflicts that occur in the management of village funds. 4) Optimization of the management, utilization and supervision of village funds can be carried out properly by increasing the capacity of village resources and potentials so that they become the carrying capacity of management, utilization and supervision as well as a tangible manifestation of the implementation of village policies in 2014.